Estratigrafía de las rocas metasedimentarias (Neoproterozoico-Cámbrico) de la Sierra de Mojotoro, Cordillera Oriental Argentina - Pamela A. Aparicio González; María Cristina Moya; Agnes Impiccini (Latin American Journal of Sedimentology and Basin Analysis, 2010)
El presente trabajo consiste en un estudio geológico detallado de las metamorfitas (Fm Puncoviscana s.l. o Complejo Puncoviscana) que constituyen el núcleo estratigráfico de la sierra de Mojotoro, Cordillera Oriental Argentina. El análisis integrado de este conjunto de rocas permitió dividir la clásica Fm Puncoviscana s.l. o Complejo Puncoviscana en tres unidades estratigráficas, que de más antigua a joven son: las Formaciones Chachapoyas, Alto de la Sierra y Guachos. La Formación Chachapoyas aflora en el flanco occidental de la sierra; está compuesta por facies de metapelitas y metaareniscas verdosas de grano muy fino, con un clivaje dominante de plano axial. Las rocas están fuertemente plegadas y afectadas por un metamorfismo dentro del campo de la anquizona alta-epizona. La Formación Chachapoyas esta intruida por diques ácidos de una edad de 533 ± 2 Ma. La facies arenosas son del tipo cuarzosas de grano fino clasto-soportadas y las facies pelíticas están compuestas por illita y clorita. La Formación Alto de la Sierra es una unidad metaarenosa, compuesta por metavaques cuarzosas, líticas y feldespáticas, donde la característica más notable es la presencia de material volcaniclástico, claramente identificable a través de corte delgado. Las arcillas de esta unidad son del tipo illita y escasos interestratificados de illita/esmectita. Las rocas fueron afectadas en un grado metamórfico tipo anquizona débil a intensa. La Formación Guachos constituye una secuencia heterolítica de metaarenisca-metapelita de coloraciones parda, pardo verdosas, en la cual se identificaron trazas fósiles de la icnofacies de Nereites. Las metaareniscas son del tipo cuarzosas donde se reconocen algunos líticos volcánicos de textura felsítica y las metapelitas están compuestas por illita, illita/clorita y clorita. Las rocas se encuentran plegadas y afectadas por un evento de deformación reconocible a escala de campo y en corte delgado. El grado de metamorfismo al cual estuvieron sujetas las rocas es dentro del campo de la anquizona intensa-epizona. The basement of Argentine Eastern Cordillera is an heterogeneous succession of siliciclastic and chemical rocks of Neoproterozoic-Early Cambrian age, identified as the "Precambrian basement" (Keidel, 1910) underlying with angular unconformity the Cambrian and Ordovician deposits of the Mesón and Santa Victoria Groups. The unit was defined as the Puncoviscana Formation (Turner, 1960) in the Santa Victoria range, and assigned to the Neoproterozoic-Cambrian (Mirré and Aceñolaza, 1972) due to the presence of Oldhamia, a trace fossil of the Lower Cambrian. However, the Puncoviscana Formation s.l. (Aceñolaza and Aceñolaza, 2005) is often adopted to identify all the basement of Eastern Cordillera, representing a heterogeneous group of rocks affected by low-grade metamorphism. The basement of the Mojotoro range is part of the 1a tecto-metamorphic zone, as defined by Willner (1990). They are part of a near-surface structural level in which the sedimentary characteristics and the original microfabric could be studied in detail (Fig. 1). From structural, stratigraphic and mineralogical information, a discontinuity (fault) could be inferred, and a new Early Cambrian stratigraphic unit named the Guachos Formation (Moya, 1998) in the Mojotoro Range can be defined. The main purpose of this contribution is to characterize the similarities and differences between the stratigraphic units of the basement in the Mojotoro Range (Lower-Middle Cambrian) in order to assess their relative stratigraphic position. The metamorphic grade was established from the cartographic material and sedimentological, petrographical and mineralogical characterization, and enabled the identification of three stratigraphic units (Fig. 1): the Chachapoyas, the Alto de la Sierra and the Guachos Formations. Satellite images and aerial photographs were used to build up a map of the studied area, with structures, lithologic contacts and sampling sites placed using GPS. The compositional studies of the field samples were carried out with a binocular magnifying lens, optic and scanning electronic microscope (SEM), and X-ray diffraction (XRD). The Chachapoyas Formation (nomen. novum.) crops out in the western flank of the range (Fig. 1), and consists of shales and very fine-grained, greenish sands, with a cleavage parallel to the axial plain (Fig. 3e). Rocks are strongly folded and affected by high anchizone-epizone grade metamorphism (Fig. 6). The unit is intruded by acidic dikes, dated at 533 ± 2 Ma, showing that the Chachapoyas Formation age is older than the other units in the Mojotoro basement (Fig. 2). Sandy facies are thin and mainly composed of grain-supported quartz arenites. Clay mineralogy corresponds to illite and clorite. Another described unit is the Alto de la Sierra Formation (nomen. novum.), composed by layers of purple and gray sands with parallel bedding, shales and feldespatic metawackes (Fig. 3a-c). Volcaniclastic material is recognized in thin sections (Fig. 4a-d), and clays mineralogy corresponds to illite and interlayer illite/smectite (Fig. 7c). The unit was affected by a weak to intense anchizone metamorphic grade (Fig. 6). A heterolitic sequence of brown to greenish brown shaly sands, with Nereites ichnofacies (Fig. 3f-h), was recognized as the Guachos Formation (Moya, 1998). The sandstones are mainly composed of quartz, and less proportions of volcaniclastic grains with felsitic texture (Fig. 3f-h). Shales are composed of illite, illite/chlorite and chlorite (Fig. 5b, d). The outcrops are folded and affected by a deformation event, a characteristic reflected in thin sections. The metamorphic grade corresponds to a high anchizone-epizone (Fig. 5a). The Guachos Formation can be correlated to the volcaniclastic rocks of Rancagua area, which presents similar facies and Nereites ichnofauna. The Rancagua succession has been studied by different authors (Lork et al., 1990; Adams et al., 2008) that described several rhyolitic detrital zircons in this unit and obtained a maximum age of sedimentation of Lower-Middle Cambrian. Finally, the fault between the Guachos Formation and the Chachapoyas Formation (Fig. 1) corresponds to a possible Neoproterozoic-Cambrian unconformity, and the acidic dikes intruded in the Chachapoyas Formation could correspond to a part of the calc-alkaline Pampean magmatic arc, defined in the Eastern Pampean ranges, with a great extension in NW Argentina, were the volcanic cover was eroded and could represent the source rock of the Alto de la Sierra and the Guachos Formations.